Maimonides, Medical Aphorisms, Hebrew Translation by Nathan ha-Meʾati - Bos, Gerrit (The Medical Works of Moses Maimonides, 2020)
The original Arabic text of Maimonides' major medical work, Medical Aphorisms, was critically edited and translated into English by Gerrit Bos in the years 2004-2017, and published in earlier volumes of the book series The Medical Works of Moses Maimonides. The present work is a new critical edition of the medieval Hebrew translation by Nathan ha-Meʾati, who was active as a translator of scientific texts in Rome in the late thirteenth century, where his colleague Zeraḥyah Ḥen had completed a translation of the same Maimonidean text in 1277, only a few years earlier. Nathan aimed to provide the general reader with a translation that was easier to understand than Zeraḥyah's translation. The present critical edition of Nathan's translation is primarily based on MS Paris, BN, héb. 1174, and not on MS Paris, BN, héb. 1173, used by Suessmann Muntner for his edition in 1959, as this copy suffers from many mistakes and corruptions.